(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Mixed martial arts (MMA) is a global sports phenomenon. In Brazil, the MMA growth has been particularly intense. This has led many athletes to try to stand out in this complex and demanding market, in which appearances are often far removed from the actual working conditions of fighters. This case study aims to show the work of MMA fighters, based on an ethnographic research carried out in an MMA event held in the city of São Paulo. Observations and conversations related to the event were recorded in a field diary, which was subsequently analyzed and interpreted from the perspective of work psychodynamics. The results obtained show that the work of MMA fighters is invisible to different social actors, which generates precariousness, fragility in their emplyment ties and the consequent trivialization of the social injustices they suffer.